Agrobacterium-Mediated Genetic Transformation of Embryogenic Callus in a Liriodendron Hybrid (L. Chinense × L. Tulipifera) - Li, Meiping; Wang, Dan; Long, Xiaofei; Hao, Zhaodong; Lu, Ye; Zhou, Yanwei; Peng, Ye; Cheng, Tielong; Shi, Jisen; Chen, Jinhui (Frontiers in Plant Science, 2022)
A highly efficient genetic transformation system of embryogenic callus (Liriodendron hybrid) by Agrobacterium-mediated genetic transformation was established and optimized. The Agrobacterium tumefaciens strain EHA105 harboring the plasmid pBI121, which contained the ß-glucuronidase (GUS) gene and neomycin phosphotransferase II (npt II) gene under the control of the CaMV35S promoter, was used for transformation. Embryogenic callus was used as the starting explant to study several factors affecting the Agrobacterium-mediated genetic transformation of the Liriodendron hybrid, including the pre-culture time and medium components of the embryogenic callus, concentrations of Geneticin (G418) selection, Agrobacterium optical density, infection duration, co-cultivation period, and delayed selection. Transformed embryogenic calli were obtained through selection on medium containing 90 mgL−1 Geneticin (G418). Plant regeneration was achieved and selected via somatic embryogenesis on medium containing 15 mgL−1 G418. We found that the optimal conditions included a pre-culture time of 2 days, and co-culture time of 3 days, an optimal infection time of 10 min, and a delayed selection time of 7 days, and these conditions, combined with an OD600 value of 0.6, remarkably enhanced the transformation rate. The results of GUS chemical tissue staining, polymerase chain reaction (PCR), real-time PCR and quantitative real-time PCR analysis demonstrated that the GUS gene had successfully expressed and integrated into the Liriodendron hybrid genome. Transformation efficiency of 60.7% was achieved for the regenerated callus clumps according to this method. Transgenic plantlets were obtained in 5 months, and the PCR analysis showed that 97.5% of plants from the tested G418-resistant lines were PCR positive. The study of the Liriodendron hybrid reported here will facilitate the insertion of functional genes into the Liriodendron hybrid via Agrobacterium-mediated transformation.